Impact of grafting and deficit irrigation on yield of melon (cucumis melo l.) (Bangladesh Journal of Botany, 2023)
An experiment was performed to evaluate the effects of grafting and deficit irrigation on yield of melon grown under different water stress conditions. The plant materials used in the study were Ünlü melon grafted on the rootstock of Ferro melon and ungrafted  Ünlü melon species. Water was applied at the level of 80, 60 and 40% of the water applied to the full irrigation level (I100=100%). Grafting significantly affected the fruit number of the plants. The fruit number in the ungrafted applications was higher than that in the grafted applications. Effects of grafting application and irrigation level on fruit weight was significant. The fruit weight in the ungrafted applications was higher than that in the grafted applications. Outcome indicated that there was no significant loss in yield, fruit number, or fruit weight of melons under application of 20% water deficit to the plants. Findings also revealed that the amount of irrigation water for melon cultivation can be safely reduced by 20% under Mediterranean climate conditions.Bangladesh J. Bot. 52(4): 925-932, 2023 (December)